Radiation-Induced Wavelength Shifts in Fiber Bragg Gratings Exposed to Gamma Rays and Neutrons in a Nuclear Reactor - G. Berkovic; S. Zilberman; Y. London; M. Rosenfeld; E. Shafir; O. Ozeri; K. Ben-Meir; A. Krakovich; T. Makmal (Sensors)
Fiber Bragg gratings (FBGs) inscribed by UV light and different femtosecond laser techniques (phase mask, point-by-point, and plane-by-plane) were exposed—in several irradiation cycles—to accumulated high doses of gamma rays (up to 124 MGy) and neutron fluence (8.7 × 1018/cm2) in a research-grade nuclear reactor. The FBG peak wavelengths were measured continuously in order to monitor radiation-induced shifts. Gratings inscribed on pure silica core fibers using near-IR femtosecond pulses through a phase mask showed the smallest shifts (<30 pm), indicating that these FBGs are suitable for temperature measurement even under extreme ionizing radiation. In contrast, the pointwise inscribed femtosecond gratings and a UV-inscribed grating showed maximal shifts of around 100 pm and 400 pm, respectively. Radiation-induced red shifts are believed to arise from gamma radiation damage, which may partially recover after irradiation is stopped. At the highest neutron exposures, grating peak blue shifts started to appear, apparently due to fiber compaction.